Precise aerodynamics measurements of a track runner using a wind-tunnel moving-belt system - Hirata, K.; Okayama, T.; Teraoka, T.; Funaki, J. (Procedia Engineering, 2012)
Concerning most of track-and-field athletics such as the marathon, it is important to elucidate the flow around track runners, and to evaluate their air resistances. We can find such studies since the 1920s. In wind-tunnel experiments which are the most effective approaches to such studies, a moving-belt system is indispensable for precise aerodynamic measurements considering the ground effect. In the present study, using a moving-belt system, the authors investigate the air resistance of a runner in solo running and in duet running. Especially for duet running, the authors reveal the optimum tandem-running formation where a following runner behind a pacemaker experiences the minimum air resistance, which is denser in comparison to the conventional wind tunnel experiment with no moving-belt system.